Cumulative iron dose and resistance to erythropoietin - Rosati, A.; Tetta, C.; Merello, J. I.; Palomares, I.; Perez-Garcia, R.; Maduell, F.; Canaud, B.; Aljama Garcia, P. (Journal of nephrology, 2015)
Introduction Optimizing anemia treatment in hemodialysis (HD) patients remains a priority worldwide as it has significant health and financial implications. Our aim was to evaluate in a large cohort of chronic HD patients in Fresenius Medical Care centers in Spain the value of cumulative iron (Fe) dose monitoring for the management of iron therapy in erythropoiesis-stimulating agent (ESA)-treated patients, and the relationship between cumulative iron dose and risk of hospitalization. Methods Demographic, clinical and laboratory parameters from EuCliD ® (European Clinical Dialysis Database) on 3,591 patients were recorded including ESA dose (UI/kg/week), erythropoietin resistance index (ERI) [U.I weekly/kg/gr hemoglobin (Hb)] and hospitalizations. Moreover the cumulative Fe dose (mg/kg of bodyweight) administered over the last 2 years was calculated. Univariate and multivariate analyses were performed to identify the main predictors of ESA resistance and risk of hospitalization. Patients belonging to the 4th quartile of ERI were defined as hypo-responders. Results The 2-year iron cumulative dose was significantly higher in the 4th quartile of ERI. In hypo-responders, 2-year cumulative iron dose was the only iron marker associated with ESA resistance. At case-mix adjusted multivariate analysis, 2-year iron cumulative dose was an independent predictor of hospitalization risk. Discussion In ESA-treated patients cumulative Fe dose could be a useful tool to monitor the appropriateness of Fe therapy and to prevent iron overload. To establish whether the associations between cumulative iron dose, ERI and hospitalization risk are causal or attributable to selection bias by indication, clinical trials are necessary.